The Effect of Coconut Fiber Usage and Clamshell Powder Replacement for Calcium Silicate Board’s Bending Strength - Zammi, Khafifulloh Al Faqih Zam; Primaningtyas, Widya Emilia; Kusminah, Imah Luluk; Riani, Novi Indah; Sakura, Rahma Rei; Alfanda, Benedicta Dian (International Journal of Marine Engineering Innovation and Research, 2025)
Calcium silicate boards (CSB) are being explored in the maritime industry due to the mechanical strength and its resintance to humidity. The common CSB comprises fiber, silica sand, and portland cement. Clamshell is one of marine waste, who has a high calcium carbonate (CaCO3) content. Coconut fiber, a natural fiber known for its high strength and durability, presents sustainable solutions for enhancing the material properties of CSB. This study explores the forming mechanism and mechanical properties of the CSB in the usage and varied volume fraction addition of coconut fiber with the varied portion replacement silica sand using clamshell powder. The bending test was performed, and the experimental results were analyzed using ANOVA, to understand the effect of the mixture composition on the bending strength of the CSB. The addition of volume fraction coconut fiber significantly improve the bending strength of the boards, while the replacement of silica sand using clamshell powder gives various result. The maximum bending strength was 13.87 ± 0.64 Mpa by 0% clamshell powder replacement in  9% coconut fiber, and significantly drop at 8.26 ± 2.20 MPa by 50% clamshell powder with 50% silica sand. In fully portion replacement of silica sand, in which the addition of 100% clamshell powder, with 9% coconut fiber, the bending strength measured at 10.29 ± 1.31 MPa. The highest results exceeding the minimum requirement in ISO-8336 category A and B (saturated condition) , class 3 (>13 MPa) standards for interior wall installations. This study providing a more robust and eco-friendly materials alternatives that supports non or maritime industry needs in while resolve the environmental issue.